Empowering Cadres by Processing Tomatoes as Nutrition to Prevent Anemia in Pregnant Women - Sari, Levi Tina; Wibisono, Wahyu; Ulfa, Maria; Agustina, Ika; Sari, Ita Novia; Handayani, Handayani; Sholichah F.H.K., Maratus (Journal of Community Service for Health, 2024)
The prevalence of anemia or a shortage of blood in pregnant women in Indonesia remains rather high, at 48.9%. This disease demonstrates that anemia is quite common in Indonesia, reaching a significant public health hazard with a prevalence of more than 40%. In 2021, Blitar Regency offered TTD of roughly 60%, which was still lower than the attainment target, therefore supplementary food was provided in the form of processed tomatoes, one of which being tomato juice and pudding. This community service project promoted health education to reduce anemia in pregnant women through discussion, films, and training on the usage of tomatoes by producing tomato fruit extract, which was then processed into tomato juice and pudding. The sample was 72 posyandu cadres from Seragi village, Talun sub-district, Blitar Regency, taken by total sampling technique. The result showed that respondent’s knowledge before being given education was in the good category of 75%, whereas knowledge about anemia in pregnancy after being given education was in the good category of 94%. Further empowerment can encourage cadres to process tomatoes into commodities that can be sold so that they have benefits for improving the economy and preventing anemia, especially for pregnant women.